STUDYING α-TERPINENE, β-CARYOPHILLENE, α-ELEMENE AND α-HUMULENE COMPOUNDS AS CORROSION INHIBITORS USING THE DENSITY FUNCTIONAL THEORY (DFT) METHOD - Triranti, Bunga Mainur; Emriadi; Adlis Santoni (JURNAL KATALISATOR, 2024)
The compounds α-Terpinene, β-Caryophillene, α-Elemene and α-Humulene are the main components of Toona sinensis leaf essential oil and have the highest % area from the research results of Toona sinensis leaf essential oil components. This research uses the Gaussian 16W program package with the Density Functional Theory (DFT) calculation method and the B3LYP/6-31G database which produces the optimal structure of the inhibitor molecule, the Highest Occupied Molecular Orbital (HOMO) contour, the Lowest Unoccupied Molecular Orbital (LUMO) contour, EHOMO, ELUMO and mulliken charge density. The inhibitor molecules analyzed were the compounds α-Terpinene, β-Charyophillene, α-Elemene and α-Humulene. Analysis of the reactivity of inhibitor molecules was carried out in the gas phase and with water as a solvent medium. Calculation of quantum chemical parameter values in the form of bandgap (∆E), electronegativity (χ), ionization potential (I), hardness (ɳ), softness (σ), electrophilicity (ω), nucleophilicity (ε), charge transfer (∆N), interaction energy (∆ѱ), back donation energy (∆Eb-d). Based on the parameter results obtained, the best compound with potential as a corrosion inhibitor is α-Terpinen. Data on bond energy, Gibbs free energy (ΔG) and entropy (ΔS), bond length and bond angle were used to determine the interaction of α-Terpinene with Fe. The interaction that occurs is a chemical interaction because the ΔG value obtained is small from -40 kJ/mol, namely -201.142 kJ/mol.